Simulation in the warehouse design and management context : a survey - Pereira, Guilherme (2011)
The dynamic character of today's competitive markets forces organizations to an incessant reassessment in an effort to respond to the continuous challenges. Warehouses as an important link in most supply chains should be an integral part of this effort. Hence, warehouses must continually be revaluated to ensure that they are consistent with both the market's demands and the management's strategies. The aim of this paper is to survey how simulation technique could represent one decision support system in the warehousing context. ©2011 EUROSIS-ETI.